ADSORPSI ZAT WARNA RHODAMIN B MENGGUNAKAN KOMPOSIT Fe3O4-AMPAS KOPI - Astuti, Resky Widya; Alimuddin, Alimuddin; Syaima, Husna (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2024)
Adsorption of Rhodamin B Dye with Fe3O4-Coffee Grounds Composite has been carried out. The purpose of this study is to determine the optimum time, optimum pH, maximum adsorption capacity and type of adsorption isotherm in rhodamin B dye with Fe3O4-Coffee grounds composite. The first stage of making Fe3O4-Coffee grounds composite using the coprecipitation method with FeCl3‧6H2O and Fe(SO4)2‧7H2O was weighed with a molar ratio of 3:2, then combined with coffee grounds. The results showed that the optimum time was obtained at 20 minutes, at the optimum pH at pH 10, and the maximum adsorption capacity obtained was 40.19 mg/g. The results of the determination of the type of isoterm in the adsorption of rhodamin b were obtained by the type of Langmuir isoterm. Keywords: Rhodamine B, Adsorption, Composite Fe3O4-coffee grounds